KESETARAAN GENDER DALAM PERSPEKTIF AL-QUR’AN: ANTARA YANG DIAKUI DAN DIATUR DENGAN ADIL - Hermansyah (STAI DI AL-HIKMAH, 2024)
Gender equality is an increasingly important issue in contemporary global social and political discourse. In the context of Islam, particularly the Qur'an, gender equality is a complex and often debated topic. The Qur'an, as the holy text of Islam, contains various verses that are interpreted differently regarding gender rights and roles. Understanding the Qur'an's perspective on gender equality is crucial for both internal comprehension within the Muslim community and for intercultural and interfaith dialogue. The Qur'an contains various commands and regulations related to gender, including women's rights, their roles in family and society, and legal rules. Some verses support principles of equality in terms of spiritual and moral rights, while others regulate different gender roles within social and legal contexts. This creates a spectrum of understanding regarding gender equality in Islam, ranging from interpretations that emphasize equality to those that view different roles as part of the social structure prescribed by the Qur'an.